The Saami shaman drums: some reflexions from an archaelogical perspective - Zachrisson, Inger (Scripta Instituti Donneriani Aboensis, 1991)
The Saami shaman drums from northern Scandinavia can be discussed from many different points of view. For an archaeologist there are other questions of interest than those which generally occupy the historian of religions. One important question is how old the known Saami drums are. The known drums are as a rule assumed to be from the seventeenth or the eighteenth centuries, when most of them were collected. It has also been thought that, because of the materials they are made of, drums could not have been preserved any longer. Another perhaps more interesting question is how old the known types of Saami drums might be. When did they acquire their 'classical' form? What did the Viking Age Saami drums look like?